Exploring competency requirements for the selection and appointment of board members and chief executive officers of state owned entities in South Africa - Meiring, Deon (University of Pretoria, 2022)
Mini Dissertation (MCom (Industrial and Organisational Psychology))--University of Pretoria, 2019.